The effect of a moving ground on the flow and aerodynamic noise behaviour of a simplified high-speed train bogie. Issue 2 (3rd April 2017) - Zhu, J. Y.; Hu, Z. W.; Thompson, D. J.
ABSTRACT: Aeroacoustic sources around the train bogie area are particularly important but involve complex flow. In this study, a numerical investigation is presented of the effect of a moving ground on the flow and aeroacoustic noise behaviour of a train bogie. These make use of the delayed detached-eddy simulation (DDES) combined with an acoustic analogy for noise prediction. First, the flow around an isolated wheel set (1:5 scale) is calculated when it is in proximity to the ground and this is compared with wind-tunnel measurements to verify the simulation. Then the flow and aerodynamic noise behaviour of a simplified high-speed train bogie at scale 1:10 with and without the ground underneath are studied numerically. It is found that a highly turbulent flow is generated within the bogie cavity and the ground increases the noise levels by 6–8 dB due to a combination of acoustic reflection from the ground and modifications to the flow.